(untitled) (SCIENCE TIME JOURNAL, 2026)
In the era of globalization, the study of languages in relation to culture has become increasingly significant. Comparative linguistic research plays a key role in identifying similarities and differences between languages and in revealing deeper insights into linguistic systems. Game names, as a part of vocabulary closely connected with culture, reflect traditions, social life, and worldview of a particular nation. This article is devoted to a comparative analysis of game names in English and Uzbek. It examines their semantic content, morphological structure, and linguocultural features. The results of the study are valuable not only for theoretical linguistics but also for practical language teaching, as they contribute to the development of intercultural communicative competence.